On the completeness of algebraic polynomials in the spaces $L_p (ℝ, dμ)$ - Bakan, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We prove that the theorem on the incompleteness of polynomials in the space $C^0_w$ established by de Branges in 1959 is not true for the space $L_p (ℝ, dμ)$) if the support of the measure μ is sufficiently dense